2003
DOI: 10.1542/peds.111.5.e586
|View full text |Cite
|
Sign up to set email alerts
|

Paranasal Sinus Findings in Children During Respiratory Infection Evaluated With Magnetic Resonance Imaging

Abstract: ABSTRACT. Objective. The spreading of acute respiratory infection into the paranasal sinuses in children is poorly defined. The main objective of this study was to evaluate the frequency and spontaneous resolution of paranasal sinus abnormalities in children with acute respiratory infection using magnetic resonance imaging (MRI).Methods. We examined 60 children with MRI (mean age: 5.7 years) with symptoms of acute respiratory infection. Twenty-six children with major abnormalities in the first MRI scan had a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 11 publications
2
27
0
3
Order By: Relevance
“…Several studies have reported the presence of incidental abnormalities of the sinuses on CT scan in asymptomatic children 1398,1399 and the occurrence of abnormal CT or MRI sinus findings in a large proportion of children with viral URIs. [1400][1401][1402] This reinforces the notion that, like in adults, every URI is essentially an episode of RS with common involvement of the paranasal sinuses by the viral process. As a result, the AAP's clinical practice guidelines 1376 state that imaging does not have a role in distinguishing acute viral from acute bacterial RS and does not have a role in uncomplicated ARS.…”
Section: Xia3 Pediatric Ars: Diagnosissupporting
confidence: 77%
“…Several studies have reported the presence of incidental abnormalities of the sinuses on CT scan in asymptomatic children 1398,1399 and the occurrence of abnormal CT or MRI sinus findings in a large proportion of children with viral URIs. [1400][1401][1402] This reinforces the notion that, like in adults, every URI is essentially an episode of RS with common involvement of the paranasal sinuses by the viral process. As a result, the AAP's clinical practice guidelines 1376 state that imaging does not have a role in distinguishing acute viral from acute bacterial RS and does not have a role in uncomplicated ARS.…”
Section: Xia3 Pediatric Ars: Diagnosissupporting
confidence: 77%
“…Kristo et al 7 estudaram crianças com infecções das vias aéreas superiores (IVAS) por RM e encontraram opacidades em 88% dos casos. Gwaltney et al 11 revelaram altos índices de anormalidades na TC de adultos com resfriado comum (até 87% dos maxilares).…”
Section: Discussionunclassified
“…O espessamento mucoso, os níveis líquidos e a opacificação total dos SPNs são alterações da RS 6 , mas também são encontradas em pacientes com resfriados, gripes, rinite e asma alérgica em proporções que variam de 33 a 88% [7][8][9][10][11] . Mesmo sem qualquer doença respiratória, esses achados frequentemente constituem achado incidental de exame [12][13][14][15][16][17][18] .…”
Section: Introductionunclassified
“…34,35 In addition, several small observational studies have assessed the use of MRI to diagnose acute sinusitis. [36][37][38] In the first, MRI was performed on a group of children 4 to 7 years of age presenting to a primary care center with any sign of respiratory infection. 36 Forty-one (68%) of 60 children had a major abnormality on imaging.…”
Section: Imagingmentioning
confidence: 99%
“…[36][37][38] In the first, MRI was performed on a group of children 4 to 7 years of age presenting to a primary care center with any sign of respiratory infection. 36 Forty-one (68%) of 60 children had a major abnormality on imaging. …”
Section: Imagingmentioning
confidence: 99%